2020
DOI: 10.1111/vsu.13423
|View full text |Cite
|
Sign up to set email alerts
|

Extended durotomy to treat severe spinal cord injury after acute thoracolumbar disc herniation in dogs

Abstract: The Infectious Diseases Data Observatory (IDDO, https://www.iddo.org) has launched a clinical data platform for the collation, curation, standardisation and reuse of individual participant data (IPD) on treatments for two of the most globally important neglected tropical diseases (NTDs), schistosomiasis (SCH) and soiltransmitted helminthiases (STHs). This initiative aims to harness the power of data-sharing by facilitating collaborative joint analyses of pooled datasets to generate robust evidence on the effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 53 publications
1
33
0
Order By: Relevance
“…Therefore, we hypothesized that extensive incision of the dura mater and hemilaminectomy in dogs with PMM could reduce intramedullary pressure. It was already observed that decompression with durotomy is possibly an effective treatment for recovering ambulation in severe acute IVDH [18,19]. These studies showed that durotomy in combination with decompression could potentially prevent the development of PMM in dogs with IVHD with NDPP of the pelvic limbs [18,19].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Therefore, we hypothesized that extensive incision of the dura mater and hemilaminectomy in dogs with PMM could reduce intramedullary pressure. It was already observed that decompression with durotomy is possibly an effective treatment for recovering ambulation in severe acute IVDH [18,19]. These studies showed that durotomy in combination with decompression could potentially prevent the development of PMM in dogs with IVHD with NDPP of the pelvic limbs [18,19].…”
Section: Discussionmentioning
confidence: 91%
“…The extend of hemilaminectomy and durotomy should be carefully considered. A previous study showed that the durotomy extending for four vertebral lengths improved functional outcome in dogs with severe spinal cord injury after acute IVDH [18]. Selection of this length was based on previous studies on the length of spinal cord swelling estimated from imaging findings [14,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of surgical interventions, there is accumulating evidence that durotomy/duroplasty may be of value in reducing the intraparenchymal spinal cord pressure (thereby improving blood flow) in humans ( 23 ), experimental animals ( 24 ) and, recently, clinical canine patients ( 25 , 26 ). This intervention has the benefit of being applicable for many hours, or even days, following an acute spinal cord injury and so could readily be translated into clinical veterinary practice.…”
Section: Interventionmentioning
confidence: 99%
“…Although there has been debate over the value of durotomy as an additional decompressive technique that might aid in restoring blood supply (and therefore retaining tissue integrity) after spinal cord injury, there are now data supporting its efficacy in clinically paralyzed dogs ( 25 , 26 ).…”
Section: Possible Clinical Trial Designs In Acute Spinal Cord Injury mentioning
confidence: 99%